THE ROLE OF IMMUNE INFLAMMATORY REACTIONS AND ENDOTHELIAL DYSFUNCTION IN MYOCARDIAL REMODELING AND PROGRESSION OF ISCHEMIC HEART DISEASE - N. E. Zakirova; A. N. Zakirova (Столичная издательская компания, 2015)
Aim. To study the role of immune inflammatory reactions and endothelial dysfunction in myocardial remodeling and progression of ischemic heart disease (IHD). Material and methods. 413 patients with IHD including 251 patients with stable and 162 patients with unstable angina were enrolled into the study. 55 healthy subjects were included into control group. Myocardial remodeling was studied by echocardiography. Immune inflammatory reactions were studied by detection of primary and secondary products of lipid peroxidation and antioxidative enzymes, pro- and antiinflammatory cytokines. Endothelial function was assessed by endothelium-dependent vasodilatation (EDVD) and levels of endothelin-1 (ET-1) and adhesion molecules. Results. Correlation analysis showed relations of indicators of lipid peroxidation and antioxidative enzymes with proinflammatory cytokines - interleukin-1β, interleukin-6, tumor necrosis factor-alpha (TGF-α) (r=-0.39; -0.54; -0.42, respectively; р<0.05) and EDVD, ET-1 and E-selectin (r=-0.44; 0.52; 0.49, respectively; р<0.05). Interrelations of lipid peroxidation products and glutathione peroxidase with hemodynamic parameters were found out, as well as between TGF-αconcentration and indicators of myocardial remodeling. Strong correlations were revealed between parameters of endothelial and myocardial functions. Conclusion. The role of immune inflammatory reactions and endothelial dysfunction in myocardial remodeling and IHD progression was established on the basis of the correlation analysis.